2013
DOI: 10.1063/1.4775357
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous germanium morphology transformation for lift-off process and substrate re-use

Abstract: The morphology of electrochemically formed mesoporous Ge double-layer and its transformations during ultra-high-vacuum annealing at 600–700 °C are investigated by scanning electron microscopy. It was found that the transformation occurs via mass transport at constant volume. The process transforms the pores into faceted spherical voids. These findings determine the optimal conditions for the transformation of the mesoporous Ge into a useful structure, which consists of a 1.8 μm thick monocrystalline Ge film wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Recently, we have reported mesoporous Ge formation by an optimized bipolar electrochemical etching of p-type Ge wafers with dimensions between 4 and 10 nm. 40,41 This substantial reduction in dimensions compared to the bulk is expected to create light emitting structures with longer wavelengths than those previously reported by Armatas. 5 In this work, we show for the first time, tunable near-infrared photoluminescence emission from mesoporous Ge, with strong direct and indirect evidences of quantum confinement effects.…”
mentioning
confidence: 88%
“…Recently, we have reported mesoporous Ge formation by an optimized bipolar electrochemical etching of p-type Ge wafers with dimensions between 4 and 10 nm. 40,41 This substantial reduction in dimensions compared to the bulk is expected to create light emitting structures with longer wavelengths than those previously reported by Armatas. 5 In this work, we show for the first time, tunable near-infrared photoluminescence emission from mesoporous Ge, with strong direct and indirect evidences of quantum confinement effects.…”
mentioning
confidence: 88%
“…Electrochemically formed porous GaAs nanostructures are particularly attractive for many applications due to their unique nanoscale properties and high surface-to-volume ratio. Furthermore, the applications of porous GaAs are very broad ranging from antireflective coating for GaAs solar cells [21], virtual substrate for InGaAs due to its weak elastic properties [22], and temporary carrier to reduce the weight of the solar cell by layer transfer processes [23, 24]. It was even shown that porous GaAs are good candidates to obtain fast response to humidity sensing [25].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of quantum confinement in the semiconductor NPs on the optical properties of semiconductors is mainly responsible for the growing interest as an attractive area of research. The interest in the basic semiconductor NPs of silicon and germanium is high as they show highly good luminescence properties at the nanoscale whereas there is no emission from them in their bulk form [3]. Further studies on Si and Ge-NPs are very interesting because of their size dependent optical properties which can lead to many technologically important applications such as optical light emitting devices [4], integrated flash memory devices [5] solar cell technology [6] and in biomedicine [7].…”
Section: Introductionmentioning
confidence: 99%